Anaplasma, Bartonella, and Rickettsia infections in Daurian ground squirrels (Spermophilus dauricus), Hebei, China - Xue, Jing; Chen, Si-Si; Xu, Ze-Yun; Wang, Fang-Ni; Wang, Jiangli; Diao, Danhong; Du, Luanying; Xie, Guang-Cheng; Guo, Wen-Ping (Frontiers in Microbiology, 2024)
Rodents have been confirmed as hosts of various vector-borne zoonotic pathogens and are important for the maintenance of these microbes in nature. However, surveillance for zoonotic pathogens is limited for many wild rodent species in China, so our knowledge of pathogen ecology, genetic diversity, and risk of cross-species transmission to humans is limited. In this study, 165 spleen samples from Daurian ground squirrels (Spermophilus dauricus) were collected from Weichang Manchu and Mongolian Autonomous County of Hebei Province, China, and Rickettsia, Bartonella and Anaplasma were identified by detecting DNA using polymerase chain reaction (PCR). Sequence analysis identified eight bacterial pathogens, R. raoultii, R. sibirica, Candidatus R. longicornii, B. washoensis, B. grahamii, B. jaculi, A. capra and Candidatus Anaplasma cinensis. Co-infection of B. grahamii and R. raoultii in one sample was observed. Our results demonstrated the genetic diversity of bacteria in Daurian ground squirrels, and contributed to the distribution of these pathogens. Six species, A. capra, R. raoultii, R. sibirica, Candidatus R. longicornii, B. washoensis and B. grahamii are known to be pathogenic to humans, indicating the potential public health risk to the local human population, especially in herders that have frequent close contact with Daurian ground squirrels and are thus exposed to their ectoparasites.